Gravis defectus discretionis iudicii w opublikowanych wyrokach Roty Rzymskiej z 2005 r. Część I - Góralski, Wojciech (Ius Matrimoniale, 2014)
On the basis of analysis of 20 sentencees of the Roma Rota of 2005 the author presents an issue of discretio iudicii, which is considered a prerequisite element of marital consensus, being a human act, assuming both an act of mind and will, thus, ability to understand, evaluate and choose freely. He also discusses essential elements of this discernment (sufficient intellectual recognition of the subject of marital consensus; sufficient critical evaluation as regards marriage as such, as well as reasons of contracting marriage and reasons of contracting marriage with a particular person; sufficient inner freedom in view of the said reasons and overcoming inner impulses). Next, he focuses on an issue of evaluative discernment (essential marital rights and obligations) and serious lack of this discernment.